GAMBARAN ALUR PENERIMAAN DAN PENYIMPANAN PERBEKALAN FARMASI DI APOTEK ASYURA MEDIKA DESA PANCIRO KABUPATEN GOWA - Basir, Hernawati; Wahyuni, Yuyun Sri; Amanda Eka Pratiwi (Akademi Farmasi Yamasi Makassar, 2023)
Management of pharmaceutical supplies is a system that plays an important role in improving pharmaceutical services. Management of pharmaceutical supplies is a cycle of activities starting from planning, procurement, receipt, storage, distribution, control, recording, and reporting, deletion, monitoring and evaluation. In the management of pharmaceutical supplies, one of the important things that is very influential is the reception and storage of pharmaceutical supplies. This research is a type of descriptive research with a qualitative approach. Data collection techniques using a system of observation, interviews and documentation. The results of this study are the acceptance at the Asyura Medika Pharmacy reaches a percentage of 86% and storage reaches a percentage of 100% including the very good category so that it can be said that the receipt and storage is in accordance with Standard Operating Procedures